THE IMPACT OF THE COVID-19 CRISIS ON THE ACTIVITIES OF THE MUNICIPALITIES IN THE REPUBLIC OF BULGARIA - N. Karatova (Trakia Journal of Sciences)
After the declaration of the state of emergency in the country, a significant human and financial resource in Bulgarian municipalities was mobilised in order to fully implement the prescriptions of health authorities and to establish an organization to ensure the safety of life and health of citizens. In addition, municipal administrations continued to carry out their normal activities and provide much of the usual public services. At the same time, the intensity of work in the various activities of the municipality has changed completely, leading to a complete restructuring of the expenditures in municipal budgets. Activities related to social services have suffered an extreme workload. Other activities in the fields of culture, sport, school and children's health, and the economy have been completely discontinued. Educational work has been thoroughly restructured. In this regard, and at the background of drastically reduced own revenues of municipalities compared to the period March - April 2019, an acute shortage of liquid resources in municipal budgets has emerged, which is now growing exponentially. The report will present in detail both the trends in municipal expenditures and the reasons for the reduction of own revenues and will outline proposals for implementing measures to address the liquidity problem of municipalities in a short and medium term perspective.